Traefik API Gateway for microservices : with Java and Python microservices deployed in Kubernetes - Sharma, Rahul; Mathur, Akshay (Apress, 2021)
Use Traefik as a load balancer or a reverse proxy for microservices-based architecture. This book covers Traefik integration for microservices architecture concerns such as service discovery, telemetry, and resiliency. The book focuses on building an in-depth understanding of Traefik. It starts with the fundamentals of Traefik, including different load balancing algorithms available, and failure handling for application resiliency. Examples are included for the failure scenarios. TLS support is explained, including scenarios of TLS termination and TLS forwarding. Traefik supports TLS termination using Let's Encrypt. Traefik deployment in prominent microservices ecosystems is discussed, including Docker and Kubernetes. Traefik is a language-neutral component. This book presents examples of its deployment with Java-based microservices. The examples in the book show Traefik integration with Jaeger/Zipkin, Prometheus, Grafana, and FluentD. Also covered is Traefik for Python-based services and Java-based services deployed in the Kubernetes cluster. By the end of the book, you will confidently know how to deploy and integrate Traefik into prominent microservices ecosystems. You will: Understand Traefik basics and its components Explore different load balancing scenarios and TLS termination Configure service discovery, circuit breakers, timeouts, and throttling Monitor Traefik using Prometheus and request tracing.